LITERATURE REVIEW: KOLABORASI INTERPROFESIONAL DALAM PRAKTIK KEPERAWATAN UNTUK MENINGKATKAN MUTU PELAYANAN, KESELAMATAN PASIEN DAN KEPUASAN KERJA TENAGA KESEHATAN - Metilda, Metilda; Dinda, Putri Rahma; Permadi, Rifki Permadi; Rohman, Rangga Nur; Anjani, Refi; Irmawati, Irmawati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The growing complexity of health care services requires more structured interprofessional collaboration to ensure service quality and patient safety. This study aims to examine the contribution of interprofessional collaboration in improving nursing care quality by reviewing national and international research. A literature review design was employed, involving 30 selected articles related to interprofessional teamwork, effective communication, and collaborative care models. The findings indicate that collaborative education, clear communication, and well-defined professional roles are key elements that strengthen team coordination. Models such as Interprofessional Education (IPE), Clinical Pathway, Team STEPPS, and multidisciplinary approaches consistently enhance service effectiveness and reduce the risk of medical errors. Nevertheless, challenges such as workload demands, competency gaps, and hierarchical organizational culture still hinder optimal collaboration. In conclusion, interprofessional collaboration is an essential strategy for advancing nursing care quality and patient safety, thus requiring strong institutional support and reliable communication systems